Educação para a vigilância do desenvolvimento infantil: formação virtual e presencial para educadores de creche - Neófiti, Cíntia Cristina (Universidade Federal de São Carlos, 2009)
The literature points out to the presence of biological and environmental risks for the child s development during their first years of life which could be influenced by factors present in several environments. In the national scenario, a day care center has been considered as one of the development contexts for being a place where they cohabit and interact, most of their time, with adults and their pairs. It is believed in this environment that there are early possibilities of risks, delays and deficiencies; the child s stimulation in the daily routine could be emphasized. In this sense, the importance of investments on the formation of educators in the perspective of having them as partners in the surveillance on the infant development foundation stands, therefore, in a preventable action in the field of Special Education. It is understood as surveillance all the activities related to the promotion of the normal development and to the detection of problems in the development. The study hereby aimed elaborating, implementing and evaluating a program of long distance capacitance to the day care center educators (Day care center educators development surveillance program Programa de Vigilância no Desenvolvimento para Educadores de Creche PROVIDEC) for the development of surveillance actions, in practice with babies. There were 47 municipal day care center educators of a medium-sized city from Sao Paulo state who composed the experimental group-EG and the control group-CG. The content of PROVIDEC considered the child development, risk factors and protection mechanisms, surveillance actions, the role of the educator at the day care center, stimulation opportunities in the day care center daily routine and health promotion. PROVIDEC counted on six virtual classes and with two present moments. This study was developed in three stages: preparation of fieldwork, invitation to the participants and composition of the groups; program elaboration; and, implementation and evaluation of the program by means of an experimental delimitation, with an experimental group and equivalent control, and, pre and post-test measures. It counted as well on pre and post-test instruments, characterization questionnaire from the participants, evaluation/perception questionnaire about the program, and the PROVIDEC. The use of those instruments demanded qualitative and quantitative seal analysis. From the results obtained, it is possible to note an increase on the repertoire of participants from the EG where it improves its answers at the moment of the post-test in 79 corporative items to the CG with only 8. From the qualitative point of view, the increase on the repertoire of the participants from the EG happen regarding the following themes related to the surveillance of development: the educator s attitudes at the moments where an abnormality or a risk for the child is noted, regarding the mechanisms of protection, to the marks of the Child Development and to the Risk Factors. Such results are discussed under the optics of the prevention actions in the field of Special Education. Future researches are suggested in the sense of the proposition of interface models among educators and basic health attention professionals to the development of surveillance operationalization actions.
Keywords: Vigilância do desenvolvimento infantil; Capacitação de educadores; Fatores de risco e proteção; Atenção primária; Ensino à distância; Development surveillance; Capacitance of educators; Risk and protection factors; Primary attention; Long distance education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL